A Pulmonary Thromboembolism Case Based on Nephrotic Syndrome that is not Previously Diagnosed - Kırkıl, Gamze; Tuğ, Tuncer; Muz, M. Hamdi; Deveci, Figen; Coşkun, Burcak; Turgut, Teyfik (Fırat University, 2005)
Pulmonary thromboembolism (PTE) is a frequent disease with a high mortality and a diffucult diagnosis. There are many secondary risk factors that can be escaped notice during early stage of PTE. One of these factors is nephrotic syndrome. Here a case presenting PTE based on nephrotic syndrome that is not previously diagnosed is presented. ©2005, Fırat Üniversitesi, Tıp Fakültesi

Pulmoner tromboemboli (PTE) sık görülen, teşhisinde zorlanılan ve mortalitesi yüksek bir hastalıktır. PTE oluşumunda erken dönemde kolayca gözden kaçabilen birçok sekonder risk faktörü bulunmaktadır. Bu faktörlerden biri de nefrotik sendromdur. Bu yazıda daha önce tanı konulmamış nefrotik sendrom zemininde gelişen pulmoner tromboemboli olgusu sunulmuştur. ©2005, Fırat Üniversitesi, Tıp Fakültesi
Daha Önce Tanı Konulmamış Nefrotik Sendrom Zemininde Gelişen Pulmoner Tromboemboli Olgusu